The geology of the Bindura granite complex in Southern Rhodesia - Bowen, David James (Rhodes University, Faculty of Science, Department of Geology, 1961)
From Introduction: The object of the investigation was to examine the variations in the granite and the relation between the granite and the surrounding metamorphosed sedimentary rocks of the Shamvaian System (Primitive). Although this object may not have been fully achieved, it has been possible to show that a wide variety of rocks is present in the area, and a few suggestions as to their origin have been made.
Keywords: Geology -- Zimbabwe -- Bindura; Granite outcrops -- Zimbabwe -- Bindura